Economic Contributions of the Agriculture, Natural Resource, and Food Industries in Florida, 2019 - Christa D. Court; João Pedro Ferreira; Robert Botta; Kelsey McDaid (EDIS)
This publication provides a summary of the economic contributions of the agriculture, natural resource, and food industries in the state of Florida in calendar year 2019. Additional details on the data sources, methodologies, and results are published in an annual report from the University of Florida, Institute of Food and Agricultural Sciences (UF/IFAS) Economic Impact Analysis Program. This information is intended to be used in support of informed decision making related to these industries.